2021
DOI: 10.1155/2021/5529509
|View full text |Cite
|
Sign up to set email alerts
|

Design and Research of Semiactive Quasi‐Zero Stiffness Vibration Isolation System for Vehicles

Abstract: The vehicle-mounted equipment is easy to be disturbed by external vibration excitations during transportation, which is harmful to the measurement accuracy and performance of the equipment. Aiming at the vibration isolation of the vehicle-mounted equipment, a semiactively controlled quasi-zero stiffness (QZS) vibration isolator with positive and negative stiffness is proposed. The vertical spring is paralleled with a magnetorheological (MR) damper, and the semiactive on-off control scheme is adopted to control… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…The ride comfort of the driver and the performance of the suspension system were mainly evaluated under the random excitation of the road surface based on the power spectrum density (PSD) G ( s 0 ) in ISO-8068 10 and white noise speed spectrum w ( t ). 21,25,26 To compare the isolation performance between the SS, RS, and AS on improving the driver’s ride comfort, the road surface roughness is also built based on the signal w ( t ) and the PSD of the road surface in the frequency region G ( f ) as follows 25,26 :…”
Section: Methodology and Nss’s Modelmentioning
confidence: 99%
See 2 more Smart Citations
“…The ride comfort of the driver and the performance of the suspension system were mainly evaluated under the random excitation of the road surface based on the power spectrum density (PSD) G ( s 0 ) in ISO-8068 10 and white noise speed spectrum w ( t ). 21,25,26 To compare the isolation performance between the SS, RS, and AS on improving the driver’s ride comfort, the road surface roughness is also built based on the signal w ( t ) and the PSD of the road surface in the frequency region G ( f ) as follows 25,26 :…”
Section: Methodology and Nss’s Modelmentioning
confidence: 99%
“…The study results of the SS 11,15,26 or the AS 12,17 in the NSS showed that the geometric dimension ratios of g 1 and g 2 ; and the stiffness ratios of b s,r and a 0 strongly influence the characteristic of the non-dimensional restoring force-deformation and the isolation performance of the driver's seat suspension system. To enhance the performance of the SS in the NSS, g 1 = 0.75, g 2 = 1.10, and b s = 0.505 were given in Ref.…”
Section: Influence Of the Nss's Design Parametersmentioning
confidence: 99%
See 1 more Smart Citation
“…A new parabolic cam-roller is designed and used in QZS isolator, and some important theoretical equations are given and the conditions for QZS characteristics are obtained [12]. In addition, CRSM also can be used as negative stiffness mechanism [13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Liu et al . (2011, 2012), Li et al . (2012a, b) studied the influence of aircraft vibration on the vibration of the airborne optoelectronic pod, proposed a two-stage vibration reduction design scheme for the optoelectronic pod and designed two new types of metal rubber shock absorbers, which effectively suppressed the transmission of vibration and made the stability accuracy of airborne optoelectronic pod reach the target.…”
Section: Introductionmentioning
confidence: 99%